Dynamics of minimal residual disease defines a novel risk-classification and the role of allo-HSCT in adult Ph-negative B-cell acute lymphoblastic leukemia. Issue 13 (10th November 2022) - Cai, Zihong; Liu, Yiqian; Tang, Bingqing; Wu, Zhengwei; Wang, Zhixiang; Lin, Ren; Xu, Xiuli; Huang, Zicong; Ou, Jiawang; Li, Xiaofang; Liu, Xiaoli; Liu, Qifa; et al.
Abstract: The prognosis of minimal residual disease (MRD) in acute lymphoblastic leukemia (ALL) patients is well established. However, the implementation of dynamic MRD for risk classification and decision-making for allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains vague. In this study, we collected multiparameter flow cytometry (MFC)-MRD data of Ph-negative B-ALL patients ( n  = 134) from the Precision-Classification-Directed-Target-Total-Therapy-ALL-2016 (PDT-ALL-2016) cohort and stratified it into high-(HR), medium-(MR), and standard-risk (SR) groups. With a median of 3.65 years follow-up (95% CI: 3.037–4.263), 3-year OS rate was 51.8 ± 8.3% in HR, compared with MR 61.5 ± 10.8% ( p  = 0.472), and SR 73.3 ± 5.9% ( p  = 0.006). Multivariate analysis shows that integrated dynamic MRD is an independent factor for overall survival. Compared to pediatric-inspired chemotherapy, allo-HSCT significantly improves the survival of the HR cohort ( p  < 0.001), but not in MR and SR. Finally, our study suggests that integrated dynamic MRD defines a novel risk-classification criteria and highlights the benefits of allo-HSCT in adult patients with Ph-negative ALL.